(3TQM OjhGf CHj GdWjHs - (3GdNhGQReis; (3CHh YHO Gddg eMeO Hf Ydj Hf EHQGgje GdgQGSj GdNhGQRej,J (B494 (3g` s
(3ChdgG (B:s
(3ddYbdGA hef gPG GdHGH bhd Gddg JYGdi (B(( (3ai adc jSHMhf (B)) (3hdjeV MjK dG jLO GdQeM eOGQG hdG GdMUGf eLGdG s
(3BNQgG (B:s
(3Je TQM OjhGf HYhf Gddg hMOgq s
(3ai CKfGA GdfSNI UaMGJ cKjQI SjFI GdJUhjQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B494s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B65 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B811s
Keywords: (3GdCOHs